NOS1AP polymorphisms reduce NOS1 activity and interact with prolonged repolarization in arrhythmogenesis. Issue 2 (15th February 2020) - Ronchi, Carlotta; Bernardi, Joyce; Mura, Manuela; Stefanello, Manuela; Badone, Beatrice; Rocchetti, Marcella; Crotti, Lia; Brink, Paul; Schwartz, Peter J; Gnecchi, Massimiliano; Zaza, Antonio
Abstract: Aims : NOS1AP single-nucleotide polymorphisms (SNPs) correlate with QT prolongation and cardiac sudden death in patients affected by long QT syndrome type 1 (LQT1). NOS1AP targets NOS1 to intracellular effectors. We hypothesize that NOS1AP SNPs cause NOS1 dysfunction and this may converge with prolonged action-potential duration (APD) to facilitate arrhythmias. Here we test (i) the effects of NOS1 inhibition and their interaction with prolonged APD in a guinea pig cardiomyocyte (GP-CMs) LQT1 model; (ii) whether pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) from LQT1 patients differing for NOS1AP variants and mutation penetrance display a phenotype compatible with NOS1 deficiency. Methods and results : In GP-CMs, NOS1 was inhibited by S-Methyl-L-thiocitrulline acetate (SMTC) or Vinyl-L-NIO hydrochloride (L-VNIO); LQT1 was mimicked by I Ks blockade (JNJ303) and β-adrenergic stimulation (isoproterenol). hiPSC-CMs were obtained from symptomatic (S) and asymptomatic (AS) KCNQ1 -A341V carriers, harbouring the minor and major alleles of NOS1AP SNPs (rs16847548 and rs4657139), respectively. In GP-CMs, NOS1 inhibition prolonged APD, enhanced I CaL and I NaL, slowed Ca 2+ decay, and induced delayed afterdepolarizations. Under action-potential clamp, switching to shorter APD suppressed 'transient inward current' events induced by NOS1 inhibition and reduced cytosolic Ca 2+ . In S (vs. AS) hiPSC-CMs, APD was longer and I CaL larger; NOS1AP and NOS1 expression and co-localization were decreased. Conclusion : The minor NOS1AP alleles are associated with NOS1 loss of function. The latter likely contributes to APD prolongation in LQT1 and converges with it to perturb Ca 2+ handling. This establishes a mechanistic link between NOS1AP SNPs and aggravation of the arrhythmia phenotype in prolonged repolarization syndromes. Graphical Abstract: